The Effect of Ethnoscience-Based Problem-Based Learning on Energy Literacy and Learning Outcomes in High School - Devia; I Nyoman Tika; Putu Artawan (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to examine the effect of a Problem-Based Learning (PBL) model integrated with ethnoscience on students’ energy literacy and learning outcomes compared to conventional PBL. A quasi-experimental design was employed using a non-equivalent control group with pre-test and post-test. The population consisted of all 67 Grade X students at SMA Negeri Satu Atap Lembongan, who were divided into experimental and control classes based on their existing class groupings. The experimental group received instruction using the ethnoscience-integrated PBL model, while the control group was taught using standard PBL. Data were collected using validated instruments assessing energy literacy (knowledge, attitudes, and behavior) and cognitive learning outcomes. Results of analyzed using MANCOVA showed that the experimental group experienced significantly higher gains in both energy literacy (p < 0.05) and learning outcomes (p < 0.05) compared to the control group. The findings suggest that integrating ethnoscience into PBL provides contextual relevance and enhances the effectiveness of science instruction. This model can serve as a culturally responsive approach to improve students' scientific understanding and engagement.